PENEGAKAN HUKUM TERHADAP JUDI ONLINE DI TORAJA UTARA (Studi Kasus Polres Toraja Utara) - Fanesa Rambo, Indhy; Salmi, Salmi; Kamal, Kasmad; Djidar, Haedar (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
Fundamentally, a bank is an institution that collects funds from the public in the form of deposits and redistributes them to the public in the form of credit. One indication that sometimes becomes a problem in banking is that it's not just about distributing credit, but how that credit can be returned according to the agreed-upon time period and interest rewards by both parties. This classifies a bank as healthy when both the distribution and return of credit can run smoothly and continue to experience improvements in terms of both quality and quantity. Non-performing loans represent one of the problems faced by banking institutions, including Bank Rakyat Indonesia (BRI), which can affect the bank's financial health, disrupt liquidity, and damage reputation. Non-performing loans occur when customers fail to pay installments according to the agreed-upon agreement. One approach that can be taken is the non-litigation route, which prioritizes peaceful resolution through negotiation and restructuring, without involving legal processes or courts. This non-litigation route has become an increasingly chosen alternative by banks in Indonesia, including Bank BRI, to address non-performing loans. The formulation of the problem in this thesis is how the mechanism for resolving non-performing loans through non-litigation channels in banking works, particularly at Bank BRI, as well as the factors that influence Bank BRI in choosing non-litigation channels as a solution for resolving non-performing loans. Meanwhile, this research was conducted with the aim of understanding the mechanism for resolving non-performing loans through non-litigation channels in banking, particularly at Bank BRI, and to identify the factors that influence Bank BRI in choosing non-litigation channels as a solution for resolving non-performing loans.